An Energy Efficient Master Auditor Node with Trust Based Secure Routing in Wireless Sensor Networks - Reddy, D. Murli Krishna; Sathya, R.; Lakshmi, V. V. A. S. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Wireless Sensor Networks (WSN) has risen in popularity as a result of the pervasiveness of communication networks and the convenience of transmitting and collecting information through these networks. Its widespread adoption can be attributed to the fact that these networks can be used in any setting without the need for costly and time-consuming environmental monitoring and engineering. To counteract malicious activity on individual nodes, trust-based approaches have recently emerged as a promising option. Implementing a reliable reputation system is the standard method used to provide trust-aware routing. When it comes to modelling the information on the behavior of nodes in a manner that accurately reflects various sources of this information, a good rating technique is essential in WSN reputation systems. Routing can be easily attacked, which can severely reduce the performance of WSNs. As most routing attacks originate from compromised nodes, conventional security mechanisms like cryptography and authentication are insufficient to counter them on their own. In order to strengthen safety and collaboration between nodes, a trust mechanism was recently implemented. The trust mechanism in routing either excludes or includes nodes in the routing procedure based on the predicted trust value. The proposed model considers a master auditor node (MAN) from the available trusted nodes that monitor the entire network analyzing each node behavior. This research proposes an Energy Efficient Master Auditor Node with Trust based Secure Routing (EE-MAN-TbSR) in Wireless Sensor Networks for trusted route selection for secured data transmission. The proposed model when contrasted with the existing models performs better in trusted route selection avoiding malicious actions in the network.